Breaking the Televisual Consensus in Chile: Popular Subjectivity and Popular Revolt in the TV Series El reemplazante - Luis Martin-Cabrera (Latin American Research Review, 2023)
This article presents a cultural analysis of the Chilean TV series El reemplazante (The substitute). The series ran on TVN (National Television of Chile) from 2012 to 2013, and it is currently available on Netflix. The show broke televisual consensus in Chile that made the production of TV series invested in promoting dissenting political viewpoints virtually impossible. As such, El reemplazante can be conceived as an antecedent of the 2019 social uprising and as an alternative model of critical TV in Chile and Latin America. The article first examines the mediation between the patriarchal and racist model of the superhero teacher and the construction of a popular subjectivity that disrupts said model. It then deals with the hyperrealist aesthetic of the show as a privileged mode of enacting a social critique on TV, and it addresses the representation of the city and its geographies of segregation as a gateway to unpacking the problematic of education in neoliberal Chile. The conclusion reflects on the abrupt cancellation of the show and the limits that the Chilean production model places on TV series with transformative intentions.